1993
DOI: 10.1107/s0108270192011417
|View full text |Cite
|
Sign up to set email alerts
|

Structure of sinoacutine

Abstract: In the title alkaloid, (9a,13a)-5,6,8,14-tetradehydro-4-hydroxy-3,6-dimethoxy-17-methylmorphinan-7-one, the mean value of three C--N--C angles is 111.0 (4) ° indicating sp 3 hybridization of the N atom.The interplanar angle between the aromatic ring A and planar ring D [maximum deviation 0.051 (5)/~ at C14] is 53.8 (1)°. The absolute configuration has been assigned to agree with the known chirality at C3 (S) [Southon & Buckingham, (1989). Dictionary of Alkaloids, p. 974. London: Chapman and Hall]. CommentSinoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It has been isolated from Sinomenium acutum and several other plant species and identified by spectral methods [6][7][8][9][10]. The crystal structure of sinoacutine isolated from Corydalis ochro-leuca was already reported [9]. The present refinement reveals a higher accuracy.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It has been isolated from Sinomenium acutum and several other plant species and identified by spectral methods [6][7][8][9][10]. The crystal structure of sinoacutine isolated from Corydalis ochro-leuca was already reported [9]. The present refinement reveals a higher accuracy.…”
Section: Discussionmentioning
confidence: 83%
“…In the course of our systematic search for bioactive substances from Chinese traditional herb medicines, we have studied the roots of S. acutum and obtained several compounds, including the title compound. It has been isolated from Sinomenium acutum and several other plant species and identified by spectral methods [6][7][8][9][10]. The crystal structure of sinoacutine isolated from Corydalis ochro-leuca was already reported [9].…”
Section: Discussionmentioning
confidence: 99%
“…An X-ray crystallographic study of nudaurine has led to a revision of the C-7 stereochemistry of this alkaloid to that shown in (157), which is the reverse of that previously deduced from the results of oxidation.200 An X-ray study of sinoacutine has confirmed the accepted structure of this alkaloid. 201 The treatment of codeine with chloroiodomethane has yielded the quaternary N-chloromethyl iodide,202 and the bromination of dihydrocodeinone in bright sunlight has given 1 -bromodihydrocodinone and 1 -bromo-1 0-hydroxydihydrocodeinone (1 58). 203 Mannich reaction of dihydrocodeinone and of 14hydroxydihydrocodeinone with dimethylamine and formaldehyde has afforded the bimolecular compounds (1 59a) and (1 59b), which presumably arise from the loss of dimethylamine from the initially formed Mannich base, followed by Diels-Alder addition of the resulting olefinic lactone to itself, as in the part structures (160).…”
Section: Alkaloids Of the Morphine Groupmentioning
confidence: 99%